Basic Life Support (BLS) Education To Increase Students' Motivation To Help Cardiac Arrest Victims - Yeni Nur Rahmayanti; Fadma Aji Pramudita; Eka Novitayanti; Betty Kusddiarningsih; Pipi Anonyma (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2025)
Basic Life Support (BLS) is an activity to clear the patient's airways, assist breathing, and maintain blood flow without the use of assistive devices. This assistance must be carried out quickly and precisely, because if the assistance is not appropriate it can cause disability, even worse, the patient can die. The purpose of this community service is to increase students' knowledge about BLS and motivation to help. The method used is education and lectures. The population in the community service is students at Tunas Harapan Vocational School, totaling 63 students with several existing problems. The results of the survey on students still have many who do not understand BLS. And from the results of the survey and interviews, most students who do not know how to help victims of cardiac arrest and some are even afraid to help. Very low knowledge and motivation and the lack of information from medical personnel regarding BLS are obstacles and problems. Therefore, it is necessary to provide education and understanding of BLS. The results showed that students experienced an increase in their knowledge of Basic Life Support (BLS) from good knowledge at 7.94% to 46.03%, and their motivation to help cardiac arrest victims increased from good knowledge at 4.76% to 58.73%. This education and motivation can provide information to students and teachers of the school so they can provide assistance to cardiac arrest victims.